Pengaruh Lompat Tali dengan Media Karet terhadap Tendangan Lurus pada Ekstrakulikuler Pencak Silat - Mubarok, Muhammad Ihsan (Advances In Social Humanities Research, 2023)
This study aims to determine the speed of straight kicks using rubber media for students of the pencak silat extracurricular activity at Pasir Eurih 05 Elementary School using a comparative quantitative approach with an experimental method using a two group pretest-posttest research design. A sample of 25 martial arts extracurricular students at Pasir Eurih 05 Elementary School was taken using purposive sampling. The sample will be tested for kick speed (post test), then do exercises using rubber media, do a kick back test (pre test). The instrument used to measure this research is the SPSS 22 application. Data processing techniques in this study using the u-test. The results of this study were obtained from data processing in hypothesis testing using the Mann Whitney U test or U test obtaining a significance value of 0.000 <0.005, which means that there is an influence in training using rubber for straight kicks. Where there are changes and increases in the speed of straight kicks in the extracurricular practice of pencak silat at Pasir Eurih 05 Elementary School.